Ultra Wide Band localization and tracking hybrid technique using VRTs - Zianal, Mohd Shamian; Abdullah, Hadi; Khan, Ijaz (International Journal of Integrated Engineering, 2012)
This research presents hybrid radar tracking technique consisting of Time Of Arrival (TOA) and Received Signal Strength (RSS) techniques. This hybrid design increases efficiency, accuracy and sensitivity of radar system. The radar used in this research is multistatic radar with one transmitter and three receivers. One common drawback in RSS and TOA techniques is high level synchronization in transmitter and receivers. The hybrid design also suffers from transmitter-receiver synchronization. To overcome TX-RX synchronization problem Virtual Reference Tags (VRTs) are used. These tags are virtually mapped over the surveillance area giving radar design different reference points from which it can accurately locate intruder and monitor its movements. Also four cases of different